In vitro degradation monitoring method

通过对含有复合涂层的可降解镁合金支架样品进行多方面的监测,解决了体外降解监测方法难以模拟体内条件的问题,实现了对镁合金支架降解行为的更准确评估,支持材料的优化和临床应用。

CN119846048APending Publication Date: 2025-04-18SHANGHAI GUOYAN MEDICAL DEVICE TESTING CENTER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411820989.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing in vitro degradation monitoring methods are difficult to fully simulate real in vivo conditions, resulting in the ideal degradation results obtained by the materials under laboratory conditions that cannot be guaranteed to be the same in the biological body.

Method used

The degradation behavior of the magnesium alloy stent was evaluated by cleaning and coating treatment, combined with inductively coupled plasma mass spectrometer, electrochemical workstation, OM and SEM, infrared and viscosity methods.

Benefits of technology

Through multi-faceted monitoring, the degradation rate of magnesium alloy stents and the protective effect of coatings can be more accurately evaluated, providing more reliable material degradation characteristics data, supporting material optimization and clinical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119846048A_ABST
    Figure CN119846048A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of in-vitro degradation, in particular to an in-vitro degradation monitoring method. The method comprises the following steps: S1, selecting a degradable magnesium alloy stent sample containing a composite coating as a research object, and carrying out cleaning and coating treatment; s2, monitoring the change of the concentration of precipitated magnesium ions by using an inductively coupled plasma mass spectrometer; s3, detecting corrosion-resistant resistance, corrosion-resistant voltage and corrosion-resistant current density by using an electrochemical workstation; s4, observing the change trend of the surface morphology and the coating thickness by using OM and SEM; and S5, monitoring the degradation and molecular weight change trend of the coating polymer by using an infrared and viscosity method. Through cleaning and coating treatment, the cleanness of the surface of the sample and the uniformity of the coating are ensured, and a reliable starting point is provided for subsequent experiments. The degradation rate of the magnesium alloy stent is evaluated by monitoring the concentration change of magnesium ions in the simulated body fluid. The kinetics and corrosion mechanism of the corrosion reaction are analyzed through the polarization curve and the alternating-current impedance spectrum data.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of in vitro degradation, in particular to an in vitro degradation monitoring method. Background Art

[0002] In vitro degradation monitoring is a technical means to simulate in vivo conditions in a laboratory environment to evaluate the degradation behavior of biodegradable materials under specific conditions. The experimental design needs to consider factors such as the selection of simulated body fluids (such as PBS phosphate buffered saline), temperature control (usually set to 37°C to simulate human body temperature), and pH adjustment to reproduce the degradation process of the material in the human body as realistically as possible. In addition, it is necessary to regularly monitor and record changes in the material's physical properties (such as mass, size, morphological changes), chemical properties (such as composition analysis of degradation products), and mechanical properties (such as tensile strength, elongation at break, etc.). Through these detailed monitoring data, researchers can fully understand the degradation characteristics of the material and provide a scientific basis for further optimization and clinical application of the material. This method not only helps to improve the safety and reliability of biomedical materials, but also accelerates the development of new products and promotes scientific and technological progress in related fields.

[0003] In the existing in vitro degradation monitoring methods, it is difficult for the in vitro environment to completely simulate the real in vivo conditions, which means that even if ideal degradation results are obtained under laboratory conditions, there is no guarantee that these materials will have the same degradation performance in the actual organism. These solutions can simulate the chemical environment in the human body to a certain extent, but they cannot replicate the complex in vivo environment. The physical conditions in in vitro experiments (such as fluid dynamics, pressure changes, etc.) are often quite different from the in vivo conditions, and these differences may affect the degradation behavior of the material. Therefore, an in vitro degradation monitoring method is provided. Summary of the invention

[0004] The purpose of the present invention is to provide an in vitro degradation monitoring method to solve the problem mentioned in the above background technology that in the existing in vitro degradation monitoring methods, the in vitro environment is difficult to completely simulate the real in vivo conditions, which means that even if the ideal degradation results are obtained under laboratory conditions, it cannot be guaranteed that these materials will have the same degradation performance in the actual organism. These solutions can simulate the chemical environment in the human body to a certain extent, but they cannot replicate the complex in vivo environment. The physical conditions in in vitro experiments (such as fluid dynamics, pressure changes, etc.) are often quite different from the in vivo conditions, and these differences may affect the degradation behavior of the material.

[0005] To achieve the above object, the present invention provides an in vitro degradation monitoring method, comprising the following steps: S1. Select a degradable magnesium alloy stent sample containing a composite coating as the research object, and perform a cleaning and coating treatment; S2. monitoring the change of the concentration of precipitated magnesium ions using an inductively coupled plasma mass spectrometer; S3. Use an electrochemical workstation to test corrosion resistance, corrosion voltage, and corrosion current density; S4. Use OM and SEM to observe the change trend of surface morphology and coating thickness; S5. Use infrared and viscosity methods to monitor the degradation and molecular weight change trend of coating polymers.

[0006] As a further improvement of the technical solution, in S1, the specific steps of selecting a degradable magnesium alloy stent sample containing a composite coating as a research object and performing a cleaning and coating treatment are as follows: S2.1. Place the magnesium alloy stent sample in an ultrasonic cleaner, add deionized water, and perform ultrasonic cleaning for 10 minutes to remove dust and impurities on the surface; S2.2. Place the magnesium alloy stent sample in a new ultrasonic cleaner, add anhydrous ethanol, and perform ultrasonic cleaning for 10 minutes to remove organic pollutants on the surface; S2.3. Place the cleaned magnesium alloy stent sample in a clean container and use a nitrogen gun to blow dry the moisture and ethanol on the surface; S2.4, preparing a suspension of nanoparticles according to the coating formula; S2.5. Pour the coating material into the liquid storage tank of the spraying device, and adjust the spraying pressure and flow rate so that the coating material is evenly sprayed on the surface of the bracket; S2.6. Slowly immerse the stent sample into the coating material, hold it for a period of time, and slowly lift the stent sample to form a uniform coating on its surface; S2.7. Place the coated stent sample in an oven and dry it at an appropriate temperature for a certain period of time to remove the solvent.

[0007] As a further improvement of the technical solution, in S2, the specific steps of monitoring the change of the concentration of precipitated magnesium ions by using an inductively coupled plasma mass spectrometer are: S3.1. Place the sample in simulated body fluid and set the temperature and pH value to ensure that the environment is close to the physiological conditions of the human body; S3.2, taking samples at predetermined time points, filtering and transferring the filtrate to an inductively coupled plasma mass spectrometer; S3.3. Use standard solutions to calibrate the instrument to ensure accurate results; S3.4, introducing the processed sample into the inductively coupled plasma mass spectrometer and starting the program for detection; S3.5. Calculate the magnesium ion concentration using the standard curve method and record the magnesium ion concentration at each time point.

[0008] As a further improvement of the technical solution, in S3.4, the specific steps of introducing the processed sample into the inductively coupled plasma mass spectrometer and starting the program for detection are: S3.41. Place the sample bottle into the autosampler and ensure that the sample bottle is positioned correctly; S3.42. Confirm the sample sequence and location information in the instrument control software; S3.43. Select the quantitative analysis method in the instrument control software to calibrate the instrument and reduce interferences; S3.44. Click the "Start" button to start the detection program; S3.45. Observe the status and signal strength of the instrument to ensure that the detection process proceeds smoothly.

[0009] As a further improvement of the technical solution, in S3.5, the specific expression for calculating the magnesium ion concentration using the standard curve method is: ; in, Indicates the concentration of magnesium ions; represents the signal intensity measured by the inductively coupled plasma mass spectrometer; represents the slope, i.e., the change in signal intensity per unit change in concentration; represents the intercept, that is, the background signal intensity of the instrument when there is no magnesium ion in the sample.

[0010] As a further improvement of the technical solution, in S3, the specific steps of using an electrochemical workstation to detect corrosion resistance, corrosion voltage, and corrosion current density are as follows: S4.1. Select a three-electrode system electrochemical cell and fix the treated magnesium alloy stent sample at the working electrode position of the electrochemical cell; S4.2, set the reference electrode and auxiliary electrode; The reference electrode is set as a saturated calomel electrode, and the auxiliary electrode is set as a platinum electrode; S4.3. Under the same simulated body fluid conditions, measure the open circuit potential, polarization curve and AC impedance spectrum of the sample; S4.4. Calculate the corrosion resistance, corrosion voltage and corrosion current density; S4.5. Record the test results.

[0011] As a further improvement of the present technical solution, in S4.4, the specific expressions for calculating the corrosion resistance, corrosion voltage and corrosion current density are: Calculate the corrosion current density using the Tafel extrapolation method: ; in, Indicates corrosion resistance current density; The linear part of the anode branch is The intersection of The linear part of the cathode branch is The intersection of Calculate the corrosion resistance voltage: ; in, Indicates corrosion resistance voltage; represents the open circuit potential; represents the current density at open circuit potential; represents the slope of the anode Tafel; Calculate the corrosion resistance: ; in, Indicates corrosion resistance; It represents the semicircle diameter of the high-frequency area.

[0012] As a further improvement of the technical solution, in S4, the specific steps of using OM and SEM to observe the surface morphology and the change trend of the coating thickness are as follows: S5.1. Gently wipe the sample surface with deionized water and dust-free paper to remove surface contaminants; S5.2. For macroscopic morphology observation, select OM and place the sample directly on the stage; S5.3. For microscopic morphology observation, select SEM, fix the sample on the sample stage, and perform conductive treatment to prevent charging effect; S5.4. Adjust the magnification of the microscope to ensure that the features on the sample surface can be clearly observed; S5.5. Take images of the sample surface from multiple angles and positions to ensure that the entire sample surface is covered, and record the surface morphology characteristics at different degradation stages; Among them, surface morphological features include porosity and cracks; S5.6. For OM, estimate the coating thickness by comparing the color differences in different areas; S5.7 For SEM, use line scan or cross-section analysis to accurately measure coating thickness; S5.8. Prepare cross sections of samples using a focused ion beam; S5.9. Use software tools to measure the thickness of the coating and record the data; S5.10. Record the coating thickness data at each time point in a table, draw a curve of coating thickness change over time, and analyze its change trend.

[0013] As a further improvement of the technical solution, in S5, the specific steps of monitoring the degradation and molecular weight change trend of the coating polymer by infrared and viscosity methods are as follows: S6.1. Analyze samples using Fourier transform infrared spectroscopy and compare spectral changes at different time points to evaluate changes in polymer structure; S6.2, indirectly reflect the change of polymer molecular weight by measuring the viscosity of the solution; S6.3, as the degradation process proceeds, the polymer chains break, causing the viscosity of the solution to decrease; S6.4. Use a rotational viscometer to measure the viscosity of the sample solution at different time points under the same conditions.

[0014] As a further improvement of the technical solution, in S6.2, the specific steps of indirectly reflecting the change of the molecular weight of the polymer by measuring the viscosity of the solution are: S6.21, dissolving the coating polymer samples at different degradation time points in a solvent; S6.22. Stir the solution thoroughly to ensure that the sample is completely dissolved, and filter the solution through a microporous filter to remove undissolved particles; S6.23. Pour the prepared sample solution into the measuring cup of the viscometer, start the instrument, and record the viscosity value at each time point. S6.24. According to the Mark-Houwink equation, the change in molecular weight of the polymer can be indirectly estimated by the change in viscosity.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. In this in vitro degradation monitoring method, cleaning and coating treatments are used to ensure the cleanliness of the sample surface and the uniformity of the coating, providing a reliable starting point for subsequent experiments. The degradation rate of the magnesium alloy stent is evaluated by monitoring the concentration changes of magnesium ions in simulated body fluids. The kinetics and corrosion mechanism of the corrosion reaction are analyzed through polarization curves and AC impedance spectroscopy data.

[0016] 2. In this in vitro degradation monitoring method, the porosity, cracks and other morphological features of the sample surface are observed by OM and SEM to evaluate the uniformity and density of the sample surface. By measuring the change in coating thickness, the protective effect and degradation rate of the coating are evaluated to ensure the integrity of the coating during the degradation process. By comparing the surface morphology at different time points, the degradation process of the sample and the change trend of the coating are intuitively displayed. By FTIR spectral analysis, the chemical structure changes of the coating polymer, such as the degradation of functional groups and the breakage of molecular chains, are evaluated. By measuring the viscosity of the solution, the molecular weight change of the polymer is indirectly inferred and the degree of polymer degradation is evaluated. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1The figure is a flow chart of the overall method of the present invention. DETAILED DESCRIPTION

[0018] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Example: See also Figure 1 As shown, this embodiment provides an in vitro degradation monitoring method, comprising the following steps: S1. Select a degradable magnesium alloy stent sample containing a composite coating as the research object, and perform a cleaning and coating treatment; In this example, the degradable magnesium alloy stent sample containing the composite coating was selected as the research object by inductive coupling, and the specific steps of cleaning and coating treatment were as follows: S2.1. Place the magnesium alloy stent sample in an ultrasonic cleaner, add deionized water, and perform ultrasonic cleaning for 10 minutes to remove dust and impurities on the surface; Specifically, an ultrasonic cleaner is a device that uses the cavitation effect produced when ultrasonic waves propagate in liquids to remove dirt from the surface of objects. When ultrasonic waves propagate in a liquid medium, a series of rapid high-pressure and low-pressure areas are formed. These changes cause tiny bubbles to form in the liquid (i.e., cavitation). When these bubbles burst rapidly, strong shock waves are generated, which effectively remove dirt, grease, and other impurities attached to the surface of the object; S2.2. Place the magnesium alloy stent sample in a new ultrasonic cleaner, add anhydrous ethanol, and perform ultrasonic cleaning for 10 minutes to remove organic pollutants on the surface; S2.3. Place the cleaned magnesium alloy stent sample in a clean container and use a nitrogen gun to blow dry the moisture and ethanol on the surface; S2.4, preparing a suspension of nanoparticles according to the coating formula; Specifically, a suspension of nanoparticles refers to a stable mixture formed by uniformly dispersing solid particles with a size usually ranging from 1 to 100 nanometers in water or other liquid media. This mixture exhibits unique physical and chemical properties due to the small size and large specific surface area of ​​the nanoparticles, such as enhanced optical, magnetic or catalytic activity; S2.5. Pour the coating material into the liquid storage tank of the spraying device, and adjust the spraying pressure and flow rate so that the coating material is evenly sprayed on the surface of the bracket; S2.6. Slowly immerse the stent sample into the coating material, hold it for a period of time, and slowly lift the stent sample to form a uniform coating on its surface; S2.7. Place the coated stent sample in an oven and dry it at an appropriate temperature for a certain period of time to remove the solvent. Use an ICP-MS to monitor the change in the concentration of precipitated magnesium ions; S2. monitoring the change of the concentration of precipitated magnesium ions using an inductively coupled plasma mass spectrometer; In this example, the specific steps of monitoring the change of the concentration of precipitated magnesium ions using an inductively coupled plasma mass spectrometer are as follows: S3.1. Place the sample in simulated body fluid and set the temperature and pH value to ensure that the environment is close to the physiological conditions of the human body; Specifically, a simulated body fluid similar to human physiological conditions is prepared, such as phosphate buffered saline (PBS), ensuring that the pH value is about 7.4 and the temperature is maintained at 37°C; S3.2, taking samples at predetermined time points, filtering and transferring the filtrate to an inductively coupled plasma mass spectrometer; Specifically, the specific steps of sampling at a predetermined time point, filtering and transferring the filtrate to an inductively coupled plasma mass spectrometer are as follows: According to the experimental design, a certain volume of liquid sample is taken from the simulated body fluid at a predetermined time point (such as 1 day, 3 days, 7 days, etc.). The sample liquid is filtered using a filter membrane with a pore size of 0.45μm or smaller to remove possible particulate matter and ensure the normal operation of the inductively coupled plasma mass spectrometer. The filtered sample should be immediately transferred to a clean container and clearly marked with the sampling time and number. If necessary, it can be stored in a refrigerator for a short period of time for analysis; S3.3. Use standard solutions to calibrate the instrument to ensure accurate results; Specifically, standard solution calibration of an instrument refers to the process of using a standard solution of known concentration to adjust the analytical instrument so that its measured value matches the true value. This process ensures that the instrument's measurement results are accurate and reliable. It is often used in chemical analysis, environmental monitoring, food testing and other fields.

[0020] S3.4, introducing the processed sample into the inductively coupled plasma mass spectrometer and starting the program for detection; In this example, the specific steps of introducing the processed sample into the inductively coupled plasma mass spectrometer and starting the program for detection are: S3.41. Place the sample bottle into the autosampler and ensure that the sample bottle is positioned correctly; S3.42. Confirm the sample sequence and location information in the instrument control software; S3.43. Select the quantitative analysis method in the instrument control software to calibrate the instrument and reduce interferences; Specifically, quantitative analysis methods include external standard method, internal standard method, standard addition method and isotope dilution method; Among them, the specific steps of the external standard method are: Prepare a series of standard solutions with known concentrations, such as 0.1 mg / L, 0.5 mg / L, 1 mg / L, 5 mg / L, 10 mg / L, etc.; The standard solutions were sequentially introduced into the inductively coupled plasma mass spectrometer, and the signal intensity at each concentration was recorded; Perform linear regression analysis of signal intensity versus known concentration using the instrument software or external data analysis software; The specific steps of the internal standard method are: Choose an internal standard that does not interfere with the detection of the target element and has similar physicochemical properties to the target element, such as scandium (Sc) or indium (In); Prepare the internal standard into a solution with a known concentration, for example, 10 mg / L; Add the same concentration of internal standard solution to all standard solutions and samples; The standard solutions were sequentially introduced into the inductively coupled plasma mass spectrometer, and the signal intensities of the target elements and the internal standard were recorded.

[0021] The specific steps of the standard addition method are: The processed sample is divided into several portions, and standard solutions of different concentrations are added to each portion to form a series of spiked samples; Each spiked sample was sequentially introduced into the inductively coupled plasma mass spectrometer, and the signal intensity of each sample was recorded; Perform a linear regression analysis of the signal intensity and the concentration of the added standard solution using the instrument software or external data analysis software.

[0022] The specific steps of the isotope dilution method are: Select an isotope standard with a different mass number than the target element, such as 25Mg or 26Mg; Prepare isotope standards into solutions of known concentrations; Add the same concentration of isotope standard solution to all samples; The processed samples were introduced into ICP-MS and the signal intensities of the target elements and isotope standards were recorded.

[0023] S3.44. Click the "Start" button to start the detection program; S3.45. Observe the status and signal strength of the instrument to ensure that the detection process proceeds smoothly.

[0024] S3.5. Calculate the magnesium ion concentration using the standard curve method and record the magnesium ion concentration at each time point.

[0025] In this example, the specific expression for calculating the magnesium ion concentration using the standard curve method is: ; in, Indicates the concentration of magnesium ions; represents the signal intensity measured by the inductively coupled plasma mass spectrometer; represents the slope, i.e., the change in signal intensity per unit change in concentration; represents the intercept, that is, the background signal intensity of the instrument when there is no magnesium ion in the sample.

[0026] Specifically, in the in vitro degradation monitoring method, the specific role of using the standard curve method to calculate the magnesium ion concentration is to establish a linear relationship between signal intensity and concentration through a standard solution of known concentration, thereby accurately converting the signal intensity of an unknown sample into magnesium ion concentration. This ensures the reliability and accuracy of the magnesium ion concentration data at each time point, providing a scientific basis for evaluating the degradation behavior of magnesium alloy stents in simulated body fluids.

[0027] S3. Use an electrochemical workstation to test corrosion resistance, corrosion voltage, and corrosion current density; In this example, the specific steps for using an electrochemical workstation to test corrosion resistance, corrosion voltage, and corrosion current density are as follows: S4.1. Select a three-electrode system electrochemical cell and fix the treated magnesium alloy stent sample at the working electrode position of the electrochemical cell; S4.2, set the reference electrode and auxiliary electrode; The reference electrode is set as a saturated calomel electrode, and the auxiliary electrode is set as a platinum electrode; S4.3. Under the same simulated body fluid conditions, measure the open circuit potential, polarization curve and AC impedance spectrum of the sample; Specifically, under the same simulated body fluid conditions, the steps of measuring the open circuit potential, polarization curve and AC impedance spectrum of the sample are as follows: Prepare simulated body fluid similar to human physiological conditions, such as phosphate buffered saline (PBS), ensuring that the pH value is approximately 7.4 and the temperature is maintained at 37 °C.

[0028] Measuring open circuit potential (OCP): Immerse the sample in simulated body fluid and wait for a period of time (usually 10-30 minutes) to allow the sample to reach electrochemical equilibrium; Start the electrochemical workstation and record the open circuit potential (OCP) of the sample.

[0029] Measuring polarization curves: Set parameters: Set the polarization curve test parameters in the electrochemical workstation, such as scan rate (usually 0.167mV / s), potential range, etc. Record data: Start the polarization curve test and record the current density of the sample at different potentials.

[0030] Measurement of electrochemical impedance spectroscopy (EIS): Set parameters: Set the AC impedance spectrum test parameters in the electrochemical workstation, such as frequency range (usually 100kHz to 10mHz), amplitude (usually 5mV), etc. Record data: Start the EIS test and record the impedance spectrum of the sample at different frequencies.

[0031] S4.4. Calculate the corrosion resistance, corrosion voltage and corrosion current density; In this example, the specific expressions for calculating corrosion resistance, corrosion voltage, and corrosion current density are: The corrosion resistance current density is calculated using the Tafel extrapolation method (the linear parts of the anode and cathode branches are selected from the polarization curve for Tafel extrapolation): ; in, Indicates corrosion resistance current density; The linear part of the anode branch is The intersection of The linear part of the cathode branch is The intersection of Calculate the corrosion resistance voltage: ; in, Indicates corrosion resistance voltage; represents the open circuit potential; represents the current density at open circuit potential; represents the slope of the anode Tafel; Calculate the corrosion resistance: ; in, Indicates corrosion resistance; It represents the semicircle diameter of the high-frequency area.

[0032] S4.5. Record the test results.

[0033] S4. Use OM and SEM to observe the change trend of surface morphology and coating thickness; In this example, the specific steps for observing the surface morphology and coating thickness change trend using OM and SEM are as follows: S5.1. Gently wipe the sample surface with deionized water and dust-free paper to remove surface contaminants; S5.2. For macroscopic morphology observation, select OM and place the sample directly on the stage; S5.3. For microscopic morphology observation, select SEM, fix the sample on the sample stage, and perform conductive treatment to prevent charging effect; S5.4. Adjust the magnification of the microscope (for SEM, the working distance and accelerating voltage also need to be adjusted to obtain the best image quality) to ensure that the features on the sample surface can be clearly observed; S5.5. Take images of the sample surface from multiple angles and positions to ensure that the entire sample surface is covered, and record the surface morphology characteristics at different degradation stages; Among them, surface morphological features include porosity and cracks; Specifically, the surface morphology analysis is: Analyze the change trend of porosity and judge the uniformity and density of the sample surface; Observe the generation and development of cracks and evaluate the mechanical stability and corrosion resistance of samples; S5.6. For OM, estimate the coating thickness by comparing the color differences in different areas; S5.7 For SEM, use line scan or cross-section analysis to accurately measure coating thickness; S5.8. Prepare cross sections of samples using a focused ion beam; S5.9. (Under SEM, select appropriate magnification and image the cross section) Use software tools to measure the thickness of the coating and record the data. S5.10. Record the coating thickness data at each time point in a table, draw a curve of coating thickness change over time, and analyze its change trend.

[0034] Specifically, the coating thickness analysis is: Analyze the change of coating thickness over time and evaluate the protective effect and degradation rate of the coating; Check the uniformity of the coating in different areas to assess the quality of the coating.

[0035] S5. Use infrared and viscosity methods to monitor the degradation and molecular weight change trend of coating polymers.

[0036] In this example, the specific steps for monitoring the degradation and molecular weight change trend of the coating polymer using infrared and viscosity methods are as follows: S6.1. Analyze samples using Fourier transform infrared spectroscopy and compare spectral changes at different time points to evaluate changes in polymer structure; Specifically, the process of analyzing samples using Fourier transform infrared spectroscopy is as follows: Collect coating polymer samples at different degradation time points (e.g., 0 h, 24 h, 48 h, 72 h, etc.); Grind the sample into fine powder, mix it with potassium bromide (KBr), and press it into a transparent sample sheet, or directly coat it on an infrared window; Turn on the FTIR instrument and preheat to a stable state; Scan the background spectrum first to ensure the stability of the background spectrum; Place the prepared sample piece into the sample slot and scan it. Record the FTIR spectrum at each time point; Use software tools to perform baseline correction on spectra and remove background noise; Identify and analyze characteristic peaks in the sample spectrum, such as characteristic absorption peaks of functional groups such as C=O, CO, and CH; The spectra at different time points were compared to observe the changes in the intensity and position of the characteristic peaks and to evaluate the changes in the polymer structure.

[0037] S6.2, indirectly reflect the change of polymer molecular weight by measuring the viscosity of the solution; In this example, the specific steps of indirectly reflecting the change of polymer molecular weight by measuring the viscosity of the solution are: S6.21, dissolving the coating polymer samples at different degradation time points in a solvent; S6.22. Stir the solution thoroughly to ensure that the sample is completely dissolved, and filter the solution through a microporous filter to remove undissolved particles; S6.23. Pour the prepared sample solution into the measuring cup of the viscometer, start the instrument, and record the viscosity value at each time point. S6.24. According to the Mark-Houwink equation, the change in molecular weight of the polymer can be indirectly estimated by the change in viscosity.

[0038] Specifically, the Mark-Houwink equation is: ; in, It represents the intrinsic viscosity; represents one of the constants related to the polymer and the solvent; It indicates the molecular weight of the polymer; represents one of the constants related to the polymer and the solvent; S6.3, as the degradation process proceeds, the polymer chains break, causing the viscosity of the solution to decrease; S6.4. Use a rotational viscometer to measure the viscosity of the sample solution at different time points under the same conditions.

[0039] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only preferred examples of the present invention, and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. An in vitro degradation monitoring method, characterized in that: The following steps are involved: S1. Select a degradable magnesium alloy stent sample containing a composite coating as the research object, and perform a cleaning and coating treatment; S2. monitoring the change of the concentration of precipitated magnesium ions using an inductively coupled plasma mass spectrometer; S3. Use an electrochemical workstation to test corrosion resistance, corrosion voltage, and corrosion current density; S4. Use OM and SEM to observe the change trend of surface morphology and coating thickness; S5. Use infrared and viscosity methods to monitor the degradation and molecular weight change trend of coating polymers.

2. The in vitro degradation monitoring method according to claim 1, characterized in that: In S1, a degradable magnesium alloy stent sample containing a composite coating is selected as a research object, and the specific steps of cleaning and coating treatment are as follows: S2.

1. Place the magnesium alloy stent sample in an ultrasonic cleaner, add deionized water, and perform ultrasonic cleaning for 10 minutes to remove dust and impurities on the surface; S2.

2. Place the magnesium alloy stent sample in a new ultrasonic cleaner, add anhydrous ethanol, and perform ultrasonic cleaning for 10 minutes to remove organic pollutants on the surface; S2.

3. Place the cleaned magnesium alloy stent sample in a clean container and use a nitrogen gun to blow dry the moisture and ethanol on the surface; S2.4, preparing a suspension of nanoparticles according to the coating formula; S2.

5. Pour the coating material into the liquid storage tank of the spraying device, and adjust the spraying pressure and flow rate so that the coating material is evenly sprayed on the surface of the bracket; S2.

6. Slowly immerse the stent sample into the coating material, hold it for a period of time, and slowly lift the stent sample to form a uniform coating on its surface; S2.

7. Place the coated stent sample in an oven and dry it at an appropriate temperature for a certain period of time to remove the solvent.

3. The in vitro degradation monitoring method according to claim 1, characterized in that: In S2, the specific steps of monitoring the change of the concentration of precipitated magnesium ions by using an inductively coupled plasma mass spectrometer are: S3.

1. Place the sample in simulated body fluid and set the temperature and pH value to ensure that the environment is close to the physiological conditions of the human body; S3.2, taking samples at predetermined time points, filtering and transferring the filtrate to an inductively coupled plasma mass spectrometer; S3.

3. Use standard solutions to calibrate the instrument to ensure accurate results; S3.4, introducing the processed sample into the inductively coupled plasma mass spectrometer and starting the program for detection; S3.

5. Calculate the magnesium ion concentration using the standard curve method and record the magnesium ion concentration at each time point.

4. The in vitro degradation monitoring method according to claim 3, characterized in that: In S3.4, the specific steps of introducing the processed sample into the inductively coupled plasma mass spectrometer and starting the program for detection are: S3.

41. Place the sample bottle into the autosampler and ensure that the sample bottle is positioned correctly; S3.

42. Confirm the sample sequence and location information in the instrument control software; S3.

43. Select the quantitative analysis method in the instrument control software to calibrate the instrument and reduce interferences; S3.

44. Click the "Start" button to start the detection program; S3.

45. Observe the status and signal strength of the instrument to ensure that the detection process proceeds smoothly.

5. The in vitro degradation monitoring method according to claim 3, characterized in that: In S3.5, the specific expression for calculating the magnesium ion concentration using the standard curve method is: ; in, Indicates the concentration of magnesium ions; represents the signal intensity measured by the inductively coupled plasma mass spectrometer; represents the slope, i.e., the change in signal intensity per unit change in concentration; represents the intercept, that is, the background signal intensity of the instrument when there is no magnesium ion in the sample.

6. The in vitro degradation monitoring method according to claim 1, characterized in that: In S3, the specific steps of using an electrochemical workstation to detect corrosion resistance, corrosion voltage, and corrosion current density are as follows: S4.

1. Select a three-electrode system electrochemical cell and fix the treated magnesium alloy stent sample at the working electrode position of the electrochemical cell; S4.2, set the reference electrode and auxiliary electrode; The reference electrode is set as a saturated calomel electrode, and the auxiliary electrode is set as a platinum electrode; S4.

3. Under the same simulated body fluid conditions, measure the open circuit potential, polarization curve and AC impedance spectrum of the sample; S4.

4. Calculate the corrosion resistance, corrosion voltage and corrosion current density; S4.

5. Record the test results.

7. The in vitro degradation monitoring method according to claim 6, characterized in that: In S4.4, the specific expressions for calculating the corrosion resistance, corrosion voltage and corrosion current density are: Calculate the corrosion current density using the Tafel extrapolation method: ; in, Indicates corrosion resistance current density; The linear part of the anode branch is The intersection of The linear part of the cathode branch is The intersection of Calculate the corrosion resistance voltage: ; in, Indicates corrosion resistance voltage; represents the open circuit potential; represents the current density at open circuit potential; represents the slope of the anode Tafel; Calculate the corrosion resistance: ; in, Indicates corrosion resistance; It represents the semicircle diameter of the high-frequency area.

8. The in vitro degradation monitoring method according to claim 1, characterized in that: In S4, the specific steps of using OM and SEM to observe the change trend of surface morphology and coating thickness are as follows: S5.

1. Gently wipe the sample surface with deionized water and dust-free paper to remove surface contaminants; S5.

2. For macroscopic morphology observation, select OM and place the sample directly on the stage; S5.

3. For microscopic morphology observation, select SEM, fix the sample on the sample stage, and perform conductive treatment to prevent charging effect; S5.

4. Adjust the magnification of the microscope to ensure that the features on the sample surface can be clearly observed; S5.

5. Take images of the sample surface from multiple angles and positions to ensure that the entire sample surface is covered, and record the surface morphology characteristics at different degradation stages; Among them, surface morphological features include porosity and cracks; S5.

6. For OM, estimate the coating thickness by comparing the color differences in different areas; S5.7 For SEM, use line scan or cross-section analysis to accurately measure coating thickness; S5.

8. Prepare cross sections of samples using a focused ion beam; S5.

9. Use software tools to measure the thickness of the coating and record the data; S5.

10. Record the coating thickness data at each time point in a table, draw a curve of coating thickness change over time, and analyze its change trend.

9. The in vitro degradation monitoring method according to claim 1, characterized in that: In S5, the specific steps of monitoring the degradation and molecular weight change trend of the coating polymer by infrared and viscosity methods are as follows: S6.

1. Analyze samples using Fourier transform infrared spectroscopy and compare spectral changes at different time points to evaluate changes in polymer structure; S6.2, indirectly reflect the change of polymer molecular weight by measuring the viscosity of the solution; S6.3, as the degradation process proceeds, the polymer chains break, causing the viscosity of the solution to decrease; S6.

4. Use a rotational viscometer to measure the viscosity of the sample solution at different time points under the same conditions.

10. The in vitro degradation monitoring method according to claim 9, characterized in that: In S6.2, the specific steps of indirectly reflecting the change of the polymer molecular weight by measuring the viscosity of the solution are: S6.21, dissolving the coating polymer samples at different degradation time points in a solvent; S6.

22. Stir the solution thoroughly to ensure that the sample is completely dissolved, and filter the solution through a microporous filter to remove undissolved particles; S6.

23. Pour the prepared sample solution into the measuring cup of the viscometer, start the instrument, and record the viscosity value at each time point. S6.

24. According to the Mark-Houwink equation, the change in molecular weight of the polymer can be indirectly estimated by the change in viscosity.